Human factors' role in distance healthcare simulation. Issue 1 (March 2023) - Bailey, Shannon K. T.; Hughes, Ashley M.; Ray, Jessica M.; Miller, Geoffrey; Vora, Samreen; Scerbo, Mark W.
As educators seek to optimize the utility of distance simulation for healthcare education, several challenges are present in the design, delivery, and evaluation of simulation-based training (SBT) that align with best practices in human factors. The planned outcome of this panel is a strengthening of the collaboration between human factors/ergonomics (HF/E) and healthcare simulation communities with practical tools that can be used to optimize distance healthcare training. Content proposed as part of the current effort should inform the development of strategic partnerships between simulationists, medical education, and HF/E professionals. We anticipate that the panel will be of interest to scientists and practitioners alike who perform work within the medical simulation space. Although the panel is formed with a focus on the needs identified for distance simulation training, panelists will be asked how human factors techniques can be beneficial to simulation in healthcare more broadly.